DEVELOPMENT OF ANIMAL-THEMED SNAKES AND LADDERS GAME MEDIA BASED ON THE ADDIE MODEL FOR EARLY CHILDREN AT KEMALA BHAYANGKARI KINDERGARTEN, WAIKABUBAK - Rusmala, Aprilia; Fatirul, Achmad Noor; Hartono, Hartono (Department of Early Childhood Education, Universitas Bina Bangsa Getsempena, 2025)
This study aims to develop a snakes and ladders game learning media with an animal theme using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model for early childhood at Kemala Bhayangkari Kindergarten in Waikabubak. The background of this study is the limited learning media that are interesting, interactive, and appropriate to the learning characteristics of early childhood. The study uses a qualitative descriptive approach with data obtained through validation sheets, questionnaires, and feedback from design experts, media experts, material experts, colleagues, and students. Data analysis was carried out descriptively to assess the feasibility and practicality of the product. The validation results showed that the design experts gave a score of 95%, media experts 96%, material experts 73%, and colleagues 90%, all of which are in the very feasible category. User trials also showed a high level of practicality with a score of 94% in small groups, 86% in medium groups, and 88% in large groups. These findings indicate that the snakes and ladders game media is easy to use, interesting, and supports children's understanding of the learning material. This learning medium has been proven to increase children's enthusiasm, motivation, and engagement during the learning process. Overall, the research results confirm that the ADDIE-based Snakes and Ladders game is a suitable alternative for effective and enjoyable learning media in early childhood education.